Efficient Degradation of Methyl Orange Over TiO2 and Poly(styrene sulfonate) Thin Films Supported on Glass Slides - Qu, Xiaolin (Asian Journal of Chemistry, 2012)
Photocatalytic nanocomposite films with different number of bilayers were prepared on microscopic glass slides via an electrostatic layer-by-layer self-assembly method. Atomic force microscopy measurement was used to observe surface morphology of layer-by-layer films. The atomic force microscopy results prove that TiO2 nanoparticles are successfully incorporated into the thin films. Photocatalytic activity of TiO2-containing multilayer films was evaluated by measuring the degradation efficiency of methyl orange. Examination of the effects of experimental factors shows that photodegradation efficiency of methyl orange increases with increasing the number of bilayers of (PSS/TiO2)n films and the highest removal efficiency is obtained when the acidity of solution is 2. The kinetic data demonstrate that the photocatalytic degradation of methyl orange conforms to the apparent first-order reaction dynamics. Immobilization of catalysts on glass slides solves the problem of recovery and may lower the costs of wastewater treatment.